2020
DOI: 10.1049/iet-pel.2019.0510
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature electrical performances and physics‐based analysis of p‐GaN HEMT device

Abstract: High-temperature electrical performances of enhancement-mode (E-mode) high electron mobility transistor with ptype Gallium Nitride (GaN) gate cap are evaluated here. The physics-based mechanisms behind the behaviours are also analysed by the simulations and analytical models. For static electrical performances, the changes of GaN bandgap and the interface states or traps are considered to be influential factors for the little variations of threshold voltage (V T). Meanwhile, the on-state resistance increases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The conductivity of GaN increases with temperature due to the increased ionization of impurities and defects, which produces free carriers. Researchers [38] also found that the high-temperature p-GaN HEMT devices threshold voltage fluctuations are minor and mainly impacted by GaN's bandgap and interface states or obstacles. The decline in transconductance and rise in on-resistance primarily originate from the reduction in carrier mobility.…”
Section: Temperaturementioning
confidence: 99%
“…The conductivity of GaN increases with temperature due to the increased ionization of impurities and defects, which produces free carriers. Researchers [38] also found that the high-temperature p-GaN HEMT devices threshold voltage fluctuations are minor and mainly impacted by GaN's bandgap and interface states or obstacles. The decline in transconductance and rise in on-resistance primarily originate from the reduction in carrier mobility.…”
Section: Temperaturementioning
confidence: 99%
“…The physical mechanism behind the degradation effects for pulsed and prolonged V GS bias stress on the p-GaN gate HEMT is explained in the Figure 9a,b. In view of the Schottky gate contact of the studied device, where the metal/p-GaN hetero-structure acts as Schottky junction diode and the p-GaN/AlGaN/GaN structure acts as p-i-n junction diode, and respective junction capacitances [38,39]. Under negative gate bias, the J Schottky is forward biased, with small voltage drop on it.…”
Section: Influenced Degradation Mechanism and Analyzationsmentioning
confidence: 99%
“…Due to the Schottky gate contact of the p-GaN gate HEMTs, the metal/p-GaN structure performs as a Schottky diode (D J1 in figure 8), the p-GaN/AlGaN/GaN structure performs as a p-i-n diode (D J2 in figure 8), and C J1 and C J2 are the junction capacitances of D J1 and D J2 , respectively [16]. At the reverse gate bias, the D J1 is forward-biased with a decreased depletion width in the p-GaN layer.…”
Section: Dominant Degradation Mechanisms and Analyzationsmentioning
confidence: 99%
“…At a high temperature, ionized holes in the p-GaN cap will also increase [16]. At the same negative V gs bias, ionized holes in the p-GaN cap can provide a more positive charge to balance the voltage drift induced by the negative gate voltage.…”
Section: Dominant Degradation Mechanisms and Analyzationsmentioning
confidence: 99%